THE EFFECTS OF DIFFERENT WATER FLOW RATES ON THE SURVIVAL RATE OF BLUE CRAB (Portunus pelagicus) ZOEA IV - MEGALOPA STAGES - Sri Rejeki (JOURNAL OF COASTAL DEVELOPMENT, 2007)
Blue crab (Portunus pelagicus) is a potential marine crustacean’s commodity. The increase demand both local and international market of the blue crab result in the culture development of this species. The larval stage of blue crab, especially at zoea IV to megalopa, plays an important rule on the successful of the production of marketable size under culture condition.Low survival rate of zoea IV to megalopa stage mostly due to their photo taxis behavior, thus, they are trapped at the water surface. Management of water flow rate on the zoea IV holding tank may be able to reduce their mortality rate and can reach megalopa stage successfully. The water flow rate management would keep the zoea in the suspension as well as improving the water quality, i.e. increases the dissolved oxygen in the water.This investigation was done to find out the effects of different water flow rates on the survival rate of blue crab (Portunus pelagicus) zoea IV stage. The tested animal was blue crab at zoea IV stage which undergoes an investigation up to megalopa stage. An experimental method with a Completely Randomized Design was applied. The 5 (five) treatments of different water flow rates were used, i.e.: A (0,25 l/minute), B (0,5 l/minute), C (0,75 l/minute), D (1,0 l/minute), E (0,0 l/minute). Each treatment was replicated three times.The results shows that different water flow rates gave a highly significant difference (P<0,01) on the survival rate of blue crab zoea IV - megaloga stage. The highest survival rate at the end of the experiment (at megalopa stage) was at treatment C (0,75 l/minute): 30,44%